Divulgação científica e a universidade no YouTube: o canal Click Ciência da UFSCar - Simardel Dantas, Melina (2023)
In modern societies, science is basis for and social, political and economic debates and decision-making. However, we are witnessing a detachment between science and society that leads to a trust decrease in scientific research and depreciation of science. Thereby we understand that scientific dissemination is a tool for rapprochement between science and society, by sharing scientific content to a wide audience, informing, educating and including the population in discussions about science and technology. If before the press was the main source of scientific dissemination, nowadays, with digital media and social networks occupying a large part of people's lives, communicating science in the virtual environment is essential for its democratization. Scientific dissemination on YouTube has become a popular method for scientists and science enthusiasts to share their knowledge with a wide audience. Therefore, our objective is to analyse the university's open science dissemination practices by studying the Click Science channel, produced by the Open Interactivity Laboratory for Dissemination of Scientific and Technological Knowledge at the Federal University of São Carlos (Laboratório Aberto de Interatividade para Disseminação do Conhecimento Científico e Tecnológico da Universidade Federal de São Carlos - LAbI UFSCar). We studied the relationships between science and society and the characteristics of scientific communication and dissemination to contextualize the relevance of scientific popularization for both researchers and population. Sociability and socialization practices in digital media were addressed to better understand society's relationship with online communication, presenting YouTube as a scientific dissemination tool for universities. We also investigated the university's scientific dissemination practices, strategies and challenges in the digital environment through analysis of Click Ciência channel. Based on the channel playlists and on videos with the highest number of views, we focussed on content that targeted the public, seeking to understand what makes a production attractive to the audience. We understand that following and adapting to current communication trends and changes is vital for scientific dissemination and for the relationship between science and society. These transformations have been constant and variable, which requires continuous studies and research.